2011
DOI: 10.1186/1750-1326-6-51
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator activator receptor gamma coactivator-1alpha (PGC-1α) improves motor performance and survival in a mouse model of amyotrophic lateral sclerosis

Abstract: BackgroundAmyotrophic lateral sclerosis (ALS) is a devastating neurodegenerative disease that affects spinal cord and cortical motor neurons. An increasing amount of evidence suggests that mitochondrial dysfunction contributes to motor neuron death in ALS. Peroxisome proliferator-activated receptor gamma co-activator-1α (PGC-1α) is a principal regulator of mitochondrial biogenesis and oxidative metabolism.ResultsIn this study, we examined whether PGC-1α plays a protective role in ALS by using a double transgen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
81
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(88 citation statements)
references
References 34 publications
5
81
1
Order By: Relevance
“…Our findings now demonstrate that muscle‐intrinsic changes triggered by PGC‐1α are sufficient to affect motor coordination and balance in old mice. Prior work revealed that central nervous system‐specific expression of PGC‐1α is essential for motor function (Lucas et al., 2012; Zhao et al., 2011). Our present data would suggest that skeletal muscle possibly initiates a retrograde signaling to the nervous system with a similar outcome, but further studies would be needed to test this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings now demonstrate that muscle‐intrinsic changes triggered by PGC‐1α are sufficient to affect motor coordination and balance in old mice. Prior work revealed that central nervous system‐specific expression of PGC‐1α is essential for motor function (Lucas et al., 2012; Zhao et al., 2011). Our present data would suggest that skeletal muscle possibly initiates a retrograde signaling to the nervous system with a similar outcome, but further studies would be needed to test this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…The regions of the brain such as hippocampus, substantia nigra, and the striatum are particularly susceptible to attack by free radicals [110,111]. The oxidativestress state has been also implicated in several neurodegenerative diseases such as Alzheimer's [112], Parkinson's [113], Huntington's, lateral amyotrophic sclerosis [114], and multiple Sclerosis [115].…”
Section: Neurodegenrative Diseasesmentioning
confidence: 99%
“…Studies using resveratrol, a polyphenolic compound that activates SIRT1 and other targets, have shown mixed effects in the SOD1 G93A mouse model of ALS, with some dosing regimens showing protection and others indicating no effect on disease progression (Han, Choi, Soon Shin, & Kang, 2012; Kim et al, 2007; Mancuso et al, 2014; Markert, Kim, Gifondorwa, Childers, & Milligan, 2010; Song, Chen, & Zhang, 2014). Overexpressing PGC1α slows ALS‐related pathologies in SOD1 G93A mice (Zhao et al, 2011), and more directly, elevating SIRT1 expression using the prion promoter has shown lifespan extension in the SOD1 G93A low copy transgenic mouse line (Watanabe et al, 2014). However, these findings do not address the focal site of action for SIRT1 or explain why an antiaging protein would impact ALS.…”
Section: Introductionmentioning
confidence: 99%